A perturbation in glutathione biosynthesis disrupts endoplasmic reticulum morphology and secretory membrane traffic in Arabidopsis thaliana - Au, K; Pérez-Gõmez, J; Neto, H; Müller, C; Meyer, A; Fricker, M; Moore, I (Wiley, 2012)
To identify potentially novel and essential components of plant membrane trafficking mechanisms we performed a GFP-based forward genetic screen for seedling-lethal biosynthetic membrane trafficking mutants in Arabidopsis thaliana. Amongst these mutants, four recessive alleles of GSH2, which encodes glutathione synthase (GSH2), were recovered. Each allele was characterized by loss of the typical polygonal endoplasmic reticulum (ER) network and the accumulation of swollen ER-derived bodies which accumulated a soluble secretory marker. Since GSH2 is responsible for converting γ-glutamylcysteine (γ-EC) to glutathione (GSH) in the glutathione biosynthesis pathway, gsh2 mutants exhibited γ-EC hyperaccumulation and GSH deficiency. Redox-sensitive GFP revealed that gsh2 seedlings maintained redox poise in the cytoplasm but were more sensitive to oxidative challenge. Genetic and pharmacological evidence indicated that γ-EC accumulation rather than GSH deficiency was responsible for the perturbation of ER morphology. Use of soluble and membrane-bound ER markers suggested that the swollen ER bodies were derived from ER fusiform bodies. Despite the gross perturbation of ER morphology, gsh2 seedlings did not suffer from constitutive oxidative ER stress or lack of an unfolded protein response, and homozygotes for the weakest allele could be propagated. The link between glutathione biosynthesis and ER morphology and function is discussed.